An experimental study on a novel cylinder harvester made of L-shaped piezoelectric coupled beams with a high efficiency. (1st December 2020) - Xie, Xiangdong; Wang, Zijing; Liu, Dezheng; Du, Guofeng; Zhang, Jinfeng
Abstract: In view of the unsatisfactory utilization efficiency of the piezoelectric patches used in the conventional harvesters, this research develops a novel efficient cylinder energy harvester made of L-shaped piezoelectric coupled beams by fully using the positive piezoelectric effect of the piezoelectric patch. Due to lack of accurate theory model of the L-shaped beam, experimental research is employed to study the advantages of the developed harvester which includes a pair of stators, a rotor and a cylindrical shell. Sets of stator specimens, a rotor, and a cylindrical shell are customized and five groups of experiments are conducted. The influences of some factors on the output voltage and power from an L-shaped beam are tested and analyzed. The output power and peak-to-peak voltage at a resonance can easily reach up to 2.35 mW and 50 V for a piezoelectric patch with a dimension of 38 mm × 13 mm × 0.5 mm of an L-shaped beam in the vibration process. This research provides an ingenious and compact structure for energy harvesting from ambient vibration such as wind and its effectiveness and efficiency are validated through a series of experiments. Graphical abstract: Image 1 Highlights: The output voltage and power of the harvester greatly influenced by PCS thickness. The PCS length hardly has influence on its output voltage and output power density. A voltage density of 0.202 V/mm 3 is easily achieved from a miniature L-shaped beam;. An output power of 2.35 mW is easily achieved from a miniature L-shaped beam.